2021
DOI: 10.3390/ijms22094914
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Dyshomeostasis in Alzheimer’s Disease Pathogenesis

Abstract: Alzheimer’s disease (AD) is the most common age-related neurodegenerative disorder that is characterized by amyloid β-protein deposition in senile plaques, neurofibrillary tangles consisting of abnormally phosphorylated tau protein, and neuronal loss leading to cognitive decline and dementia. Despite extensive research, the exact mechanisms underlying AD remain unknown and effective treatment is not available. Many hypotheses have been proposed to explain AD pathophysiology; however, there is general consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 227 publications
(265 reference statements)
1
92
0
6
Order By: Relevance
“…Many in vitro and in vivo studies have shown that AβO exposure causes the production of reactive oxygen species (ROS), likely as a result of mitochondrial dysfunction. AβOs also induce Ca 2+ dyshomeostasis, not only in the cytosol but also in mitochondria [ 18 , 19 ]. Specifically, AβOs have been shown to increase mitochondrial Ca 2+ via the mitochondrial Ca 2+ unipolar complex [ 19 ].…”
Section: Aβos and Oxidative Stress In Admentioning
confidence: 99%
“…Many in vitro and in vivo studies have shown that AβO exposure causes the production of reactive oxygen species (ROS), likely as a result of mitochondrial dysfunction. AβOs also induce Ca 2+ dyshomeostasis, not only in the cytosol but also in mitochondria [ 18 , 19 ]. Specifically, AβOs have been shown to increase mitochondrial Ca 2+ via the mitochondrial Ca 2+ unipolar complex [ 19 ].…”
Section: Aβos and Oxidative Stress In Admentioning
confidence: 99%
“…Calcium acts as a second intracellular messenger and plays a key role in the regulation of neuronal functions, namely neural growth and differentiation, action potential, and synaptic plasticity [70]. Calcium signaling is involved in neurotransmitter release, synaptic plasticity, gene expression, and other important neuronal functions [71].…”
Section: Multifactorial Etiologymentioning
confidence: 99%
“…Progressive disruption of neuronal Ca 2+ homeostasis is one of the leading mechanisms of action of the amyloidogenic proteins Ab as the toxic species in the etiology of Alzheimer`s disease (AD) [1][2][3]. Increase in intracellular content of oligomeric Abs is believed to play a major role in the early phase of AD as their intracellular rise strongly correlates with the symptoms and have been proved to be predictive of cognitive status in AD affected patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%